2007
DOI: 10.2135/cropsci2006.10.0645
|View full text |Cite
|
Sign up to set email alerts
|

SSR Mapping and Confirmation of Soybean QTL from PI 437654 Conditioning Resistance to Reniform Nematode

Abstract: Recently, reniform nematode (Rotylenchulus reniformis Linford and Oliveira) has been recognized to be a major problem on soybean [Glycine max (L.) Merr.] in the southern USA. Planting reniform nematode–resistant soybean cultivars is the most cost effective control method. With restriction fragment length polymorphism (RFLP) markers, Pioneer Hi‐Bred International, Inc. had previously identified quantitative trait loci (QTL) on linkage group B1 (LG‐B1) and another on LG‐L associated with reniform nematode resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…Cardoso et al (2014) reported that soybean resistance to RN is inherited quantitatively based on lines evaluated from two populations of Forrest (resistant) x BR96-25619 (susceptible) and Custer (resistance) x BR96-25619 (susceptible) normal distribution from highly resistant to highly susceptible. Ha et al (2007) identified three QTLs conditioning RN resistant on Chrs. 11, 18, and 19 that explained 16, 8, and 21% of phenotypic variation, respectively from accession PI437654.…”
Section: Discussionmentioning
confidence: 99%
“…Cardoso et al (2014) reported that soybean resistance to RN is inherited quantitatively based on lines evaluated from two populations of Forrest (resistant) x BR96-25619 (susceptible) and Custer (resistance) x BR96-25619 (susceptible) normal distribution from highly resistant to highly susceptible. Ha et al (2007) identified three QTLs conditioning RN resistant on Chrs. 11, 18, and 19 that explained 16, 8, and 21% of phenotypic variation, respectively from accession PI437654.…”
Section: Discussionmentioning
confidence: 99%
“…This genetic behavior was also reported in studies on the genetic inheritance of R. reniformis resistance in soybean (Williams et al 1981, Harville et al 1985. Ha et al (2007) evaluated genotype PI 437654 with molecular markers and proved that the genes of R. reniformis resistance are close to those that control H. glycines resistance. Furthermore, these authors showed that resistance is controlled quantitatively by genes with unequal effects.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that genes that confer resistance to reniform nematodes are close to those that confer resistance to soybean cyst nematode (SCN), especially in genotypes derived from Forrest, Custer, Pickett, Hartwig, PI 437654, Peking, Centennial, PI 90763, and Cordell (Rebois et al 1970, Robbins et al 1994b, Robbins and Rakes 1996, Ha et al 2007. Most authors suggest a genetic linkage between the locus of resistance to Heterodera glycines and R. reniformis.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the studies of SCN and RKN, the advent of genetic marker technologies facilitated the identification and molecular characterization of QTL or genes for RN resistance. So far, several QTL for RN resistance and associated molecular markers were identified and mapped to chromosomes 11, 18, and 19 (LGs B1, G, and L, respectively) (Ha et al 2007;Webb et al 1995). Genetic mapping and host plant resistance genes is reviewed in more detail later in this chapter.…”
Section: Reniform Nematodementioning
confidence: 99%
“…However, developing new resistant cultivars has been challenging because of the genetic variability of nematode species, as well as the complex involvement of resistance genes Williamson 1998). Advancements in molecular marker technologies have greatly facilitated the detection and characterization of genomic regions associated with broad resistance to nematodes (Concibido et al 2004;Ha et al 2004;Ha et al 2007;Li et al 2001;Tamulonis et al 1997a;Vuong et al 2010;Wu et al 2009). Such genetic marker-trait associations can be efficiently utilized for marker-assisted selection (MAS) or genomic selection (GS), in which several resistance genes/genomic regions can be pyramided to select elite backgrounds, leading to the improvement of nematode-resistant varieties of soybean.…”
Section: Introductionmentioning
confidence: 99%